Creation of a Framework of Design Tool Characteristics to Support Evaluation and Selection of Visualisation Tools. (July 2019) - Zhang, Wenwen; Ranscombe, Charlie; Radcliffe, David; Jackson, Simon
Abstract: In Industrial Design, new design visualisation tools are emerging offering significant benefits to the designers. However, studies show alongside some benefits, new tools can also inhibit designers' creativity or cause time inefficiency if used in the wrong context. Thus, understanding which tools to use and when during the design process is increasingly necessary to ensure the best use of resources in design practice. Existing research on understanding the performance of design tools and the resulting frameworks for comparing tools are either specific to certain tools or highly generalised making evaluation across different design tools challenging. As such, this paper reports the creation of a more comprehensive framework of design tool characteristics to facilitate a better understanding of design tools and their uses. Demonstration of application of the framework is also given in the form of a case study on the use of Digital Sketching and its comparable tools with four practising designers. In conclusion, we show how the Design Tool Characteristics (DTCs) framework is an effective way to understand design tools, with further implications for design tool development.